Prospects in cadmium-contaminated water management using free-living cyanobacteria (Oscillatoria sp.) - Carralero Bon, Iván (2021)
In this study, the removal of cadmium (Cd) by free-living Oscillatoria sp. was studied. Our results showed that maximal Cd removal efficiency (~60%) by the cyanobacterial culture was achieved within 12-24 h in the presence of 5.0 or 25.0 mg/L of Cd. The mechanisms underlying this phenomenon were explored by elemental analysis and FTIR-ATR spectroscopy. It was found that metal adsorption by negatively charged functional groups in the cyanobacterial biomass was the main mechanism used by Oscillatoria sp. to remove metal from the aqueous medium, followed by Cd bioaccumulation into living cells. Additionally, Cd-exposed microalgae showed increased oxidative stress (MDA formation), a decreased dehydrogenase activity, a higher amount of soluble carbohydrates and a decreased total carotenoid concentration, as compared to the control cells. These results suggest that Oscillatoria sp. improved its antioxidative defense system under stressful conditions, through carotenoid-mediated ROS quenching and induction of carbohydrate catabolism, in order to counteract the oxidative damage and preserve the photosynthetic machinery and cellular energetics. In fact, no significant reduction in Oscillatoria sp. cell density, total protein amount, and chlorophyll a content was observed after 24-h Cd exposure, even at the highest metal concentration tested (i.e., 25.0 mg/L). Hence, the presented results are the first to describe some new insights about the metabolic and physiological behavior of living Oscillatoria sp. during Cd remediation, and open up the possibility of finding an equilibrium that maximizes metal removal performance with an active cyanobacterial metabolism, to achieve a rewarding and sustainable management of industrial metal-polluted wastewater.